PERBANDINGAN KINERJA KEUANGAN PT. BANK NUSA TENGGARA BARAT SYARIAH (BANK NTB SYARIAH) SEBELUM DAN SESUDAH KONVERSI - Reno Virlandana A (Universitas Pamulang, 2022)
The purpose of study is to see the comparison of the financial performance of NTB Syariah Bank before and after conversion. This study uses a quantitative method by observing and comparing numbers in the analysis of financial ratios such as the Liquidity Ratio represented by the Loan to Deposit Ratio (LDR), the Solvency Ratio proxied by the Capital Adequaty Ratio (CAR), and Net Performing Loan (NPL), Profitability Ratio profixed by Return On Assets (ROA) and Return On Equity (ROE), Effectiveness Ratios proxied by Operating Costs and Operating Income (BOPO) and Activity Ratios proxied by Total Assets Turnover (TATO) of NTB Syariah Bank before and after conversion by using quartely financial reports since 2016 to 2020. The results of study reveal that since oficially operating as NTB Syariah Bank on September 24, 2018 there are differences in financial performance before and after financial. Therefore, it can be concluded that the financial performance of NTB Bank before conversion is better than after conversion.